The Rise of Small-Scale Development Organisations The Emergence, Positioning and Role of Citizen Aid Actors (Taylor & Francis, 2023)
This edited volume discusses the rise, positioning and role of small-scale, voluntary development organisations in the Global North. This book presents and reflects upon unique data and analyses of a growing global community of researchers involved in this field of study located in a diverse set of countries in the Global North and South. This book presents a multi-cited perspective on this alternative development actor. The first part of the book starts from a northern perspective and from an analysis of how and why citizens actively engage in the field of international development. Starting from this understanding of this particular development actor, the second part will delve into the role of these actors in the Global South, particularly related to topics such as partnerships, embeddedness, legitimacy, accountability, exit strategies, sustainability and solidarity, all themes central to debates in the field of development. Through examples from different countries in the Global South, part two explores these themes from different standpoints and thus also provides the reader with thick descriptions.
English
Keywords: Charities, voluntary services & philanthropy; Development studies; Accountability, CIGS, Embeddedness, Exit Strategies, Global North, Global South, NGDOs, Small-Scale Development, Organisations